FORMS OF WORK IN THE ASPECT OF LEARNING IN COLLABORATION - Mamirova, Gulnoza (Журнал иностранных языков и лингвистики, 2021)
The article is devoted to the basic concepts of learning in cooperation, the advantage of this technology; the theoretical material is accompanied by examples of tasks from the experience of teaching English in the aspect of cooperation technology.